Enhancing Critical Thinking through the Team Game Tournament Cooperative Learning Approach - Revi; Iyan Setiawan; Rismawati (Yayasan Dekhalisha Global Prestise, 2025)
The problem of this study is the low critical thinking ability of students characterized by dependence on reading books and lack of initiative in solving problems independently. This study aims to analyze the Effect of the Implementation of the Team Game Tournament (TGT) Cooperative Learning Model on the critical thinking ability of class XI students in the Economics subject of SMA Negeri 1 Ciwaru. The research method used is Quasi Experimental with a Non-Equivalent Control Group design. This study involved two groups of students, namely the experimental group who received cooperative learning type Team Games Tournament (TGT) and the Control group with the Lecture Method. The results of the analysis showed that there was a significant difference in critical thinking ability between the experimental class who received the Team Games Tournament (TGT) learning model and the Control class students who received the Lecture Method. This difference can be seen from the creative thinking ability of students in the experimental class who received the Team Games Tournament (TGT) cooperative model obtained higher results compared to the Control class students who received the Lecture Method. Therefore, the use of the Team Games Tournament (TGT) cooperative learning model can improve students' critical thinking ability.